Lymphovenous Anastomosis Aids Wound Healing in Lymphedema: Relationship Between Lymphedema and Delayed Wound Healing from a View of Immune Mechanisms - Yoshida, Shuhei (Adv Wound Care (New Rochelle), 2019)
Delayed wound healing in lymphedema is assumed to be caused by two reasons, pathophysiological and immunological effects of lymphedema. The aim of this review is to establish how impaired lymphatics alter wound healing pathophysiologically and immunologically, and to propose treatment modalities that can promote wound healing in lymphedema. Lymphaticovenular anastomoses (lymphovenous anastomoses [LVAs]) were performed on patients who had recurrent cellulitis several times with lymphorrhea and developed severe ulcers that were refractory to skin grafts, flaps, and conservative therapy. The lymphorrhea and the ulcer had healed by 4 weeks. Moreover, the lymphedema improved without compression therapy. Lymphedema is characterized pathophysiologically by localized peripheral edema that compresses the microvasculature and lymphatic vasculature and impairs tissue remodeling. Another suspected mechanism is an imbalance in the differentiation of participating immune cells. Profound suppression of T helper (Th)1 cells is likely to increase the risk of infection, and excessive differentiation of Th2 cells, including M2 macrophage polarization, may promote fibrosis, which disrupts the carefully orchestrated wound healing process. Although negative-pressure wound therapy is useful for the treatment of delayed wound healing in lymphedema, LVAs may be necessary to treat the fundamental problem of lymphedema. LVAs are considered to create a bypass to the lymph nodes through which dendritic cells (DCs) can transmit antigen information to T cells. LVAs are considered to neutralize chronic inflammation by allowing more DCs to return into the circulation, thereby improving wound healing.